Manejo da fertilização potássica em cafeeiro conilon - Rodrigues, Thaimã Cristina Jesus (2017)
The cultivation of Conilon coffee in the Zona da Mata rondoniense has been done predominantly under irrigation due to the irregular distribution conditions of the precipitations. After irrigation system implantation, the application of nutrients via irrigation water increases its efficiency of use by the plants. The objective of this work was to evaluate the vegetative growth of branches and the productive performance of conilon coffee in different manure management in the Zona da Mata Rondoniense. The experiment was carried out in the municipality of Rolim de Moura, Rondônia, in a field propagated by cuttings with 18 months of age. The experimental design was a randomized complete block design with four replications. The main plot consisted of three manures of fertilization, irrigated, fertirrigated and rainfed, and the four potassium doses, 200 kg, 400 kg, 600 kg and 800 kg of K2O ha-1 were used in the subplots. Productivity, already for the evaluations of vegetative development the experiment was conducted in a scheme of sub-divided plots in time, being in the subsubparcelas the periods of evaluations (measurement of the branches). The results showed that the growth of plagiotropic branches did not differ from each other, regardless of the management of ix fertilization. Regardless of potassic fertilization, the highest and lowest vegetative growth rates are observed in the summer and winter seasons, respectively, under the conditions studied, with the highest growth from October to March, mainly influenced by the mean maximum temperature below 34ºC and precipitation. The increasing doses of potassium applied from 200 kg K2O ha-1 did not increase the vegetative growth of the coffee tree. The 20% increase in the recommended dose of potassium resulted in an increase in productivity of 200% compared to the productivity of the state of Rondônia in the 2015 harvest of 19.67 sc / ha¯¹. For the mass characteristics of 100 fruits and yield, it was not possible to establish the coherent relationship between the manure of fertilization and the doses of potassium. The split of the dose of 200 kg K2O ha-1 via irrigation, during the production of the coffee, provided an increase in the industrial yield (REND), liters of coffee per bag 60 kg (L sc⁻¹).